Hormone resistance in children: what primary care physicians need to know - Metwalley, Kotb; Farghaly, Hekma (Acta Biomedica Atenei Parmensis, 2021)
Hormone resistance is defined as a reduced or absence of target tissues responsiveness to a hormone, where the presentation is related to either a relative lack or excess of hormones. Various disorders of hormone resistance were encountered including, Laron syndrome, nephrogenic diabetes insipidus, thyroid hormone resistance syndrome, pseudohypoparathyroidism, insulin resistance, familial glucocorticoid deficiency, pseudohypoaldosteronism, X linked hypophosphatemic rickets and androgen insensitivity syndrome. The article gives a summary that presents, in concentrated form, what the primary care physicians need to know about recognition, clinical presentation, diagnosis, and management of various hormone resistance in children.